A sense of home in residential care. Issue 4 (21st November 2012) - Falk, Hanna; Wijk, Helle; Persson, Lars‐Olof; Falk, Kristin
Abstract : Moving into a residential care facility requires a great deal of adjustment to an environment and lifestyle entirely different from that of one's previous life. Attachment to place is believed to help create a sense of home and maintain self‐identity, supporting successful adjustment to contingencies of ageing. The purpose of this study was to deepen our understanding of processes and strategies by which older people create a sense of home in residential care. Our findings show that a sense of home in residential care involves strategies related to three dimensions of the environment – attachment to place, to space and attachment beyond the institution – and that the circumstances under which older people manage or fail in creating attachment, consist of psychosocial processes involving both individual and shared attitudes and beliefs. Assuming that attachment is important to human existence regardless of age, attention must be paid to optimize the circumstances under which attachment is created in residential care, and how nursing interventions can help speed up this process due to the frail and vulnerable state of most older residents.